Distribution Network Voltage Arc Suppression Method Based on Flexible Regulation of Neutral Point Potential of the New Grounding Transformer - Lifang, WU; Hao, BAI; Ke, Zhou; Zhiyong, Yuan; Xiaoyong, Yu; Jinyong, Lei; Yu, Zou; Yuan, Zhang (Frontiers in Energy Research, 2022)
Aiming at the problems that the existing arc suppression cabinet technology cannot adjust the zero sequence voltage flexibly, and the control and hardware implementation of active arc suppression equipment based on power electronics are difficult, a new method of voltage arc suppression in distribution network based on the flexible regulation of neutral point potential of new grounding transformer is proposed. From the perspective of sequence component, the variation law of the neutral point voltage before and after the closing of the tapped grounding branch of the new grounding transformer is analyzed. By selecting the appropriate initial tap position of the tap-to-ground switch, the fault phase voltage is flexibly controlled, so that the fault phase voltage is reduced to below the reignition voltage to quickly solve the influence of single-phase grounding fault, and the risk of non-fault phase insulation breakdown is reduced to ensure the stable operation of distribution network. According to the ratio of the fault phase current to the zero sequence voltage before and after the gear inputs, whether the arc suppression of single-phase grounding fault is completed is judged. Compared with power electronic products, the new grounding transformer has the advantages of high reliability, long service life and low cost, and has strong economy and applicability in engineering. The single-phase grounding fault model of 10kV distribution network is built in PSCAD/EMTDC simulation environment, and the new method of distribution network voltage arc suppression based on the flexible regulation of neutral point potential of new grounding transformer is verified. The simulation results show that the proposed method can effectively reduce the fault phase voltage to achieve the reliable arc suppression of single-phase grounding fault.